2021
DOI: 10.1101/2021.08.13.21261995
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiplex Target-Redundant RT-LAMP for Robust Detection of SARS-CoV-2 Using Fluorescent Universal Displacement Probes

Abstract: The increasing prevalence of variant lineages during the COVID-19 pandemic has the potential to disrupt molecular diagnostics due to mismatches between primers and variant templates. Point-of-care molecular diagnostics, which often lack the complete functionality of their high throughput laboratory counterparts, are particularly susceptible to this type of disruption, which can result in false negative results. To address this challenge, we have developed a robust Loop Mediated Isothermal Amplification assay w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Therefore, primer design decisions were based on performance-driven parameters such as computational estimates of primer properties (e.g., homodimers, hairpin structures, Tm, and %GC). Our recent in silico analysis revealed that our primers still have high coverage across new variants (8). The specific overlap with the U.S. Centers for Disease Control and Prevention (CDC) primers (Fig.…”
Section: Novel Modifications Of Reverse Transcription Loop-mediated I...mentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, primer design decisions were based on performance-driven parameters such as computational estimates of primer properties (e.g., homodimers, hairpin structures, Tm, and %GC). Our recent in silico analysis revealed that our primers still have high coverage across new variants (8). The specific overlap with the U.S. Centers for Disease Control and Prevention (CDC) primers (Fig.…”
Section: Novel Modifications Of Reverse Transcription Loop-mediated I...mentioning
confidence: 94%
“…Harmony also uses novel universal probes containing entirely engineered sequences (8). The 5′ FAM or 5′ TEX 615 signal probes each have a 5′ sequence region hybridized to the complementary sequence region of its quencher probe that has 3′ Iowa Black FQ or 3′ BHQ-2, respectively.…”
Section: Novel Modifications Of Reverse Transcription Loop-mediated I...mentioning
confidence: 99%
“…A number of recent reports have focused on variant panels designed to target a finite number of emergent mutations to discern variant identity, particularly in the first months of 2021. Most panels utilize RT-PCR or novel isothermal technologies (e.g., RT-LAMP, CRISPR/Cas-based, massspectrometry) to target specific polymorphisms in the S gene that have been ascribed to each of these variants 25,27,45,[48][49][50] . However, a recent deep analysis of circulating variants across the globe revealed that most of these signature mutations are not under positive selection 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The primers usually target regions in the N, S, E or ORF1ab gene; however, only one target can be used in each assay which limits its accuracy and increases the probability of false negative occurrence [38]. A multiplex RT-LAMP assay has also been developed which allows for more accurate detection since it targets two SARS-CoV-2 regions [39]. There are also tests that employ both CRISPR-Cas and RT-LAMP technology at the same time in order to circumvent some of their individual limitations [40,41].…”
Section: Rt-lampmentioning
confidence: 99%